STRATEGI KOMUNIKASI INTERPERSONAL ORANG TUA DALAM MEMBENTUK KOSEP DIRI PADA ANAK TUNARUNGU - Saraswati, Prihatin (Jurnal Socia Akademika, 2023)
The purpose of this study was to find out how parents' interpersonal communication strategies in communicating with deaf children. This type of research is descriptive qualitative research. The determination of the object uses a sample, in this case, the parents of children with special needs at AKS AKK Yogyakarta as many as three people from the Culinary Arts, Fashion Design and Makeup study programs. Sample determination technique using purposive sampling. Data collection techniques in this study utilizing observation (observation), in-depth interviews and documentation. Data analysis method using descriptive method. The results of the study are interpersonal communication strategies using effective non-verbal communication symbols that will facilitate communication in deaf children in forming their self-concept in addition to parental communication strategies for deaf children with authoritative forms with acceptance, control is equally high, quickly respond to children's needs and desires and provide an explanation of the impact of all children's behaviour so that deaf children understand their self-concept and get along is like any other normal child